Comparative Study of Patient Satisfaction, Physical Space and Medical Equipment between Governmental and Private Hospitals - Masoumeh Seidi; Akram Heidary; Ashraf Khorramy-Rad; Hoda Ahmary-Tehran (Iran University of Medical Sciences, 2009)
Background and Aim: Quality of services in hospitals should be continuously evaluated in terms of structure, process, and outcome. The purpose of this study was to comparepatient satisfaction, physical space and medical equipment between governmental and privative hospitals in Qom, Iran.   Material and Method: In this descriptive-analytcal study, 500 patients from selected Qom hospitals were recruited based on stratified random sampling. Data were collected by patient satisfaction form and assessment check lists of physical atmosphere and medical equipments. Data were analyzed by SPSS, version 11.5. The authors declare that they have no conflict of interests.   Results: Patient satisfaction in inpatient and emergency wards of governmental hospitals were, respectively %69 and %71/14. Patient satisfaction in inpatient and emergency wards of privative hospitals were %80 and %78, respectively. General and emergency wards of governmental hospitals were somewhat equipped with medical equipments. Physical atmosphere, in terms of facilities and the building, was acceptable in general and relatively acceptable in emergency wards of governmental hospitals. This atmosphere were relatively acceptable for both general and emergency wards of privative hospitals.   Conclusion: Satisfaction among patients were relatively good. It is possible to improve satisfaction through increasing the visiting time, improving quality of lavatories, and modifying personnel interactions with the patients.Also, promoting medical equipments and physical space can improve the situation according to organizational goals.